Sebuah Tinjauan Literatur Sistematis Tentang Pemilihan Lokasi Pusat Distribusi Barang Untuk Konsumen - Nasihardani, Dana; Satrio, Reno; Kahirullah, M. Fikri; Abdulrahman, Ridwan; Suroto, Kuwat (Proceeding Mercu Buana Conference on Industrial Engineering, 2023)
The rapid development of the manufacturing industry has contributed to an increase in the level of business competition. A competitive business strategy is needed to answer the challenges of business competition. The manufacturing industry is engaged in the production of consumer goods. Marketing areas that are spread across Indonesia and abroad make supply chain performance in manufacturing companies very important. This leads to the position that manufacturing companies focus more on the production process and the distribution process is handed over to third parties so that it becomes a very important part of the warehouse location selection process that will be used as a distribution center for goods to consumers. The purpose of this study is to analyze the application of the AHP and TOPSIS methods in supplier selection. The method used is systematic literature review. This tool can be multi-criteria able to be applied to manufacture small industries in the advanced competitive world in an era of destruction. Breaking down these tools will deliver cost reductions, improve service levels and will cover more areas in the supply chain.